CXCR2 Is Essential for Radiation-Induced Intestinal Injury by Initiating Neutrophil Infiltration - Jing Hu; Qian Ji; Fei Chen; Xiaoqin Gong; Chuansheng Chen; Kaijun Zhang; Ye Hua; Jinlei Wang; Rongkun Li; Xu Wang; Chunhua Dai; Ye Tian (Journal of Immunology Research)
Neutrophils, known as an important part of the immune system, are the most abundant leukocyte population in peripheral blood, but excessive recruitment will lead to tissue/organ injury. RNA sequencing showed that ionizing radiation significantly increased the expression of characteristic genes of neutrophils in intestinal tissues compared with liver and lung tissues. By clearing neutrophils with an anti-Ly6G antibody, we found that neutrophil infiltration is critical for irradiation-induced intestinal injury. CXCR2 is a G-protein-coupled receptor that mediates the migration of neutrophils by combining with its ligands. Compared with observations in liver and lung tissues, we found that CXCR2 and its ligands, including CXCL1, CXCL2, CXCL3, and CXCL5, were all significantly upregulated in irradiated intestinal tissues. Further studies showed that SB225002, an inhibitor of CXCR2, could effectively inhibit the chemotaxis of neutrophils and tissue damage mediated by the CXCL-CXCR2 signalling pathway.